Frameworks and Practices in Bioethics - Dwyer, James (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
I begin this essay with an autobiographical introduction to explain why I studied philosophy and how I came to work in bioethics. I then consider three ethical frameworks and practices that I adopted in my work in bioethics. I begin with the framework that John Rawls makes explicit, where the purpose of ethical theory is to set out aims and objectives to guide our responses to the world. Since this approach did not provide the guidance that I was looking for, I took up writing haiku as an ethical practice. I present here many examples of haiku that I wrote to pay attention to situations in life and bioethics. The hope was that paying attention would lead me to respond in better ways. Since this practice helped me more with attending than responding, I turned to a third framework. Here I explore John Dewey’s ethical framework. After characterizing this framework, I consider features that an associated practice needs to have. In a brief conclusion, I note some affinities between the second and third ethical approaches, and note that the last ethical framework adopted may just be the latest stage in trying out frameworks and practices.